Sistem Fuzzy Menggunakan Metode Sugeno dalam Akurasi Penentuan Suhu Kandang Ayam Pedaging - Darma Yunita Darmawi; Gunadi Widi Nurcahyo; Sumijan (Jurnal Informasi dan Teknologi, 2021)
Chicken meat is one of the most commonly consumed side dishes. To produce high quality chicken meat, a system is needed that makes it easy for breeders to buy chickens, one of which is the right system in determining the temperature of a broiler cage. The purpose of this study was to obtain a temperature appropriate to the age of the chickens as well as in its cultivation. In this case, the Fuzzy Sugeno method is used in an effort to build a systematic approach to generate the fuzzy rules from the input data sets given with fuzzy variables temperature, chicken age and decision. Where in each fuzzy variable there are linguistic variables, age (small, adolescent, and adult), temperature (cold, medium, and hot), decision (cold, ideal, hot). Later it will be processed with Matlab R2013a and can be implemented with Arduinno Mega 2560 using the Arduino IDE (Integrated Development Environment) programming compiler. A typical study in this study was conducted in a broiler cage with a size of approximately 40X10 m with a capacity of about 5000 broilers. The result of testing for this method is the ideal temperature according to the age and temperature of the broiler house input. From the trials that have been carried out, it can be said that the Fuzzy Sugeno method which is implemented with the Arduino Mega 2560 microcontroller can increase the accuracy of the ideal temperature in broiler brackets.